Exploring the case for investing in early years in Wales: a broad evidence review. (November 2016) - Edwards, R T; Bryning, L; Lloyd-Williams, H
Abstract: Background: Life-expectancy and healthy life-expectancy depend on the socioeconomic and wider determinants of health. At birth there is an 18·9 year difference in healthy life expectancy between the least and most deprived areas of Wales. Multidisciplinary public health policy requires that prevention interventions are increasingly assessed in terms of the financial return on investment. The aim of this study was to explore the return on investment of a broad range of early years' interventions, where possible applied to the context of Wales. Methods: We constructed a pragmatic framework to explore international and UK evidence on the relative return on investment of: devoting public sector resources to programmes and practices that support babies and young children (up to age 7 years), and their families; promoting skills development through education; and fostering positive environments that protect health assets relevant to the early years. This review was not done systematically because of the breadth of interventions considered. Rather, we used snowballing to search for literature starting with centres of excellence in the USA and UK, and recent key policy reports. We restricted our search to studies published in English during the past 20 years. Findings: We identified estimates of return on investment, mainly from the USA and UK, from investment in the child and whole family, education and skills, and a child's environment and wider community. Methods of calculating return on investment were not standardised so comparisons across programmes were problematic. We found evidence that for every £1 spent on contraceptive services between £11 and £14 in savings could be returned annually to the National Health Service (NHS) in Wales. We estimate that increasing the proportion of women who exclusively breastfeed at 4 months (presently 9% in Wales) to that recorded at birth (57%) could save the NHS in Wales £1·5 million annually in treating common early childhood diseases. Our finding that every £1 invested in adventure playgrounds could provide a return on investment of £1·32 shows the importance of physical activity and play. Interpretation: There are efficiency and equity arguments for investing in early years. Investment in early years should be considered in the same way as investment in the wider economic development across the Welsh economy. Funding: Public Health Wales.